A Calculation Method of Fragment Initial Velocity of Blast-fragmentation Warhead Based on Neural Network. Issue 1 (July 2021) - Yong, Sun; Jun, Li; Dawei, Liu; Jirong, Xue; Yan, Chen
Abstract: This paper analyzes the theoretical calculation method of the initial velocity of the static bursting disc and the factors affecting the initial velocity of the static bursting disc. On this basis, a calculation method and device of the initial velocity of the fragmentation warhead based on the neural network is proposed. The strong nonlinear mapping ability of the BP neural network and the associative memory ability of the external stimulation and input information are used to determine the initial velocity of the fragment of the kill warhead and improve the efficiency. The speed of calculation and the accuracy of the results are given.